Глобалізація і педагогіка - Анатолій Вихрущ (Pavlo Tychyna Uman State Pedagogical University, 2013)
Аналіз проблем глобалізації в сучасному світі дає підстави ставити питання про значну кількість позитивних і негативних явищ. Значна їх частина має безпосереднє відношення до педагогічної науки і практики. Відкритість і доступність інформаційного простору, зростання значущості особистісного чинника для успішного функціонування соціально-економічних систем, особливості підготовки фахівців, які будуть працювати в умовах полікультурного середовища, зумовлюють необхідність оновлення змісту, форм, методів організації виховного процесу, удосконалення освітньої політики. Анализ проблем глобализации в современном мире дает основания ставить вопрос о значительном количестве положительных и негативных явлений. Значительная их часть имеет непосредственное отношение к педагогической науки и практики. Открытость и доступность информационного пространства, рост значимости личностного фактора для успешного функционирования социально-экономических систем, особенности подготовки специалистов, которые будут работать в условиях поликультурной среды, обусловливают необходимость обновления содержания, форм, методов организации воспитательного процесса, совершенствование образовательной политики. Globalization in modern world raises different issues, both harmful and beneficial. Quite a number of them deal with educational theory and practice. The principal works by Ukrainian educationalists on globalization are analyzed. Some international approaches to globalization have been paid attention to. The author shows their interdependence, which, in its turn, results in energy and environmental crisis, moral and spiritual values devaluation, unstable political and economic situation. The article presents different globalization aspects: (1) economic aspect is shown through investments in education; (2) cultural globalization which is presented at the angle of preserving national identity, combining traditional culture and modernism; (3) educational globalization under the influence of transnational financial groups. The author makes a number of conclusions as to defining the term «pedagogy» as well as the functions it performs. The author sums us his observations with pointing to the main positive developments caused by globalizations.